Morphometric analysis of vasospastic rat femoral artery via double hemorrhage model [İkili kanama modeli i̇le rat vazospastik femoral arterin morfometrik analizi] - (:unkn) unknown (Ege University Press, 2014)
Objective: We employed a rat femoral artery model of experimental vasospasm in order to evaluate morphometric changes and a possible autoimmune response in a delayed secondary hemorrhage vasospasm. Methods: We established a vasospasm model of rat femoral arteries by using Okada's model, and evaluated vasospasmic arteries in terms of morphometric changes at first week and first month. We evaluated the effect of secondary hemorrhage, which we performed at the end of the first month, at the end of the first week after secondary hemorrhage. For the evaluation of arteries, we performed hematoxylin and eosin staining. We measured vessel wall thickness and lümen areas and compared these across all the groups. Results: We observed no significant difference between first week and first month results, in terms of vessel wall thickness and lumen area measurements. There was also no significant difference between the secondary hemorrhage results evaluated at first week (after secondary hemorrhage) and first month. However, we found a signficant difference when these results were compared to the femoral arteries of control group rats. Furthermore, we observed an excessive number of fibrous structures and amount of granulation after secondary hemorrhages. Conclusions: It was not possible for us to investigate the response of the femoral artery to secondary delayed hemorrhage and a possibly-related autoimmune mechanism. This was due to the excessive fibrous structure and granulation around the vessel, which prevented treatment of the secondary hemorrhage with vessels. Furthermore, morphological changes caused the prevention of vessel vasospasm and vasoconstriction. Finally, we believe that Okada's vasospasm model is not suitable for secondary delayed hemorrhage studies.
Keywords: Double hemorrhage; Rat femoral artery; Subarachnoid hemorrhage; Vasospasm model